Internacionalização do ensino superior em Turismo - Dias, Roberta Abalen (2016)
The aim of the thesis is to analyze the internationalization of higher education in tourism programs of federal institutions of Belo Horizonte, in Minas Gerais. To obtain the data was carried out qualitative research, exploratory, and documentary and bibliographic research. The framework formed by the theoretical investigation of the tourism, universities and higher education internationalization, verifying and then its application in the Belo Horizonte educational institutions. Identified the tourism courses structure, were identified existing international partnerships in higher education institutions studied, composing a frame of reference with the University of Girona. The theme of internationalization in tourism education is relevant, as expressed several possibilities in the academic dynamics of educational institutions. Encourages, moreover, the production of new knowledge and can be considered factor of innovation and differentiation in a competitive market, and underline the importance of tourism for economic development in Brazil and worldwide. The discussions focused on the internationalization of tourist activities and the role of the university in the process permeated all the chapters, and is a major strength of the study